The Influence of Social Media Influencer Endorsement on Purchase Intention With The Mediating Roles of Parasocial Interaction and Possession Envy - Mathea, Nessa; Laksmidewi, Dwinita (AIBPM Publisher, 2024)
This study investigates the impact of social media influencer endorsements on purchase intention while examining the mediating roles of parasocial interaction, possession envy, brand credibility, and brand attractiveness. Social media influencer endorsements have become a prominent marketing strategy for influencing consumer buying decisions, yet there is limited research on the intermediary factors involved. The research employs surveys targeting social media users experienced in influencer endorsements who regularly purchase influencer-recommended products or services. The sample includes diverse respondents across age groups and demographics. Structural Equation Modelling - Partial Least Squares (SEM-PLS) with SmartPLS software is utilized for data analysis. Findings reveal that social media influencer endorsements significantly enhance purchase intention. Parasocial interaction is identified as a mediator in the relationship between influencer endorsements and purchase intention. However, possession envy does not serve as a mediator for social media interactions' influence on purchase intention. In essence, perceived interactions with influencers and feelings of possession envy play pivotal roles in explaining the link between influencer endorsements and purchase intention. Additionally, brand attractiveness and brand credibility act as intermediaries in the impact of social media interactions on purchase intention. This study contributes valuable insights into the dynamics of influencer marketing and its effects on consumer behavior.Keywords: social media influencer endorsements, purchase intention, parasocial interaction, possession envy, brand credibility.